Passive surveillance on occurrence of deadly infectious, noninfectious and zoonotic diseases of livestock and poultry in Bangladesh and remedies (SAARC Journal of Agriculture, 2018)
Passive surveillance system was designed with the data (102,613 case records) collected from the Government Veterinary Hospitals, Bangladesh and frequency distribution of diseases was calculated during July 2010 to June 2013. Frequently occurring diseases/ disease conditions reported in livestock were fascioliasis (10.66%), diarrhoea (7.92%), mastitis (7.42%), foot and mouth disease (6.42%), parasitic gastroenteritis (6.31%), coccidiosis (5.5%), Peste des petits ruminants (PPR,5.32%), anthrax (4.19%) and black quarter (3.74%). Diarrhoea and coccidiosis were reported to occur throughout the year. The frequency of fascioliasis appeared higher in buffaloes (34%) followed by sheep (22%), goats (13%) and cattle (11%). PPR is a deadly infectious disease of goats and sheep, accounted for 20% and 13% infectivity in respective species. In chicken the most frequently occurring diseases reported were Newcastle disease (28%), fowl cholera (19%) and coccidiosis (11%). In ducks, duck viral enteritis (28%), duck viral hepatitis (17%), diarrhoea (15%), coccidiosis (10%) and intestinal helminthiasis (10%) were the commonest diseases reported in Bangladesh. Few other endemic diseases of livestock and poultry like Tuberculosis, brucellosis, avian influenza, duck anatipestifer, Marek’s disease, Gumboro disease, avian tuberculosis, mycoplasmosis, dermatophilosis etc. were not included in the hospital data sheet. Financial hurdles persist in a country like Bangladesh, imposing difficulties onto the surveillance and early reporting of the disease outbreaks; these diseases are, therefore, stubbornly prevalent. Development of technological and knowledgeable man power, in time surveillance and early warning of disease outbreak are the key to protect animal and public health and produce safe food of animal origin.SAARC J. Agri., 16(1): 129-144 (2018)